Macro-Concepts of Rod and Makosh: A Comparative Analysis of Motivating Signs - Vayrakh, Yu. V.; Ibraimova, G. O. (Вестник Кемеровского государственного университета, 2022)
The article describes the macro-concepts Rod (a Slavic female deity) and Makosh (a Slavic female deity) in the Russian linguistic culture. It is the first attempt to analyze these macro-concepts in terms of conceptual signs. The authors studied the lexemes of Rod and Makosh / Mokosh as the main representatives of the macro-concepts in the National Corpus of the Russian Language, as well as compared their cognitive signs. The methods included descriptive, interpretive, and conceptual linguistic analyses. The macro-concept of Makosh revealed 33 cognitive signs, which were divided into 11 groups: 1. (Divine) motherhood (four signs): goddess, Mother of God / Virgin Mary, poppy head, crown. 2. Natural objects and phenomena (four signs): rain, star, earth, horns / cornucopia. 3. Fertility (two signs): abundance, harvest. 4. Spirits of nature (one sign): mermaids / pitchforks. 5. Kinship (six signs): wife, mother, grandparent, relationship, family, elder sister. 6. Functions (four signs): thunderbearer, spinner, creator, mistress. 7. Relationships (one sign): care. 8. Evaluation (one sign): good. 9. Person (two signs): girl, woman. 10. Fate (four signs): share, lot, fate, luck. 11. Cult (four signs): idol, Paraskeva Pyatnitsa (Saint Paraskevi of Iconium), Rozhanitsa (a Slavic female deity), treba (prayer) / sacrifice. The structure of the macro-concept Rod had 35 cognitive features, which were divided into 13 groups: 1. (Divine) fatherhood (two features): god, God-father. 2. Natural objects and phenomena (three features): star, lightning, sky. 3. Fertility (one sign): harvest. 4. Kinship (four signs): father, grandparent, kinship, family. 5. Functions (five signs): agriculture, ruler, justice, creation, creator. 6. Relationships (two signs): care, protection. 7. Evaluation (three signs): good, deceit, adultery. 8. Fate (two signs): share, fate. 9. Cult (five signs): idol, feast, Stribog (a Slavic male deity), treba (prayer) / sacrifice, Yarilo (a Slavic male deity). 10. Success (four signs): crown, profit, prosperity, success. 11. Place of birth (one feature): Motherland. 12. Property (one sign): strength. 13. People (two signs): civilization, humanity. These signs reflected the peculiarities of the Russian linguistic mentality, which preserved the memory of the cult of Rod (literally, kin) and Makosh (Mother Goddess). This cult was consistently reproduced in veneration of the Mother Earth and family deities Rod and Makosh, the divine parents of people. Christian aspects manifested themselves as the image of Virgin Mary and God the Father. The macro-concepts of Rod and Makosh appeared to have a number of overlapping cognitive features: good, deity (god, goddess), destiny, care, star, idol, progenitor, kinship, family, fate, creator, prayer / sacrifice, harvest.